Isues in cultural tourism studies - Smith, Melanie K. (Routledge, 2009)
The extensively revised second edition of Issues in Cultural Tourism Studies provides a new framework for analyzing the complexity of cultural tourism and its increasing globalization in existing as well as emergent destinations of the world. The book will focus in particular on the need for even more creative tourism strategies to differentiate destinations from each other using a blend of localized cultural products and innovative global attractions." "The book explores many of the most pertinent issues in heritage, arts, festivals, indigenous, ethnic and experiential cultural tourism in urban and rural environments alike. This includes policy and politics; impact management and sustainable development; interpretation and representation; marketing and branding; and regeneration and planning. As well as exploring the inter-relationships between the cultural and tourism sectors, local people and tourists, the book provides suggestions for more effective and mutually beneficial -- collaboration